A meta-analysis of the efficacy of intraperitoneal cisplatin for the front-line treatment of ovarian cancer - Hess, L M; Benham-Hutchins, M; Herzog, T J; C-H, Hsu; Malone, D C; Skrepnek, G H; Slack, M K; Alberts, D S (International journal of gynecological cancer, 2007)
Ovarian cancer is the fourth leading cause of cancer death among women in the United States. First-line chemotherapy offered to patients with ovarian cancer generally consists of an intravenous (IV) platinum plus taxane regimen and has remained virtually unchanged for the past 10 years. A number of recently completed phase III randomized trials in the United States have reported improved progression-free survival (PFS) and/or overall survival (OS) with the intraperitoneal (IP) administration of cisplatin. The purpose of this study was to pool the published data to perform a meta-analysis of randomized trials of IP cisplatin in the initial chemotherapy treatment of ovarian cancer patients. This study was initiated to obtain a more valid estimate of the therapeutic impact of IP treatment for these patients. A search strategy was initiated that searched published findings of randomized trials of IP cisplatin therapy from multiple sources from January 1990 through January 2006. Six randomized trials of 1716 ovarian cancer patients were identified and included in this analysis. The pooled hazard ratio (HR) for PFS of IP cisplatin as compared to IV treatment regimens is 0.792 (95% CI: 0.688–0.912, P = 0.001), and the pooled HR for OS is 0.799 (95% CI: 0.702–0.910, P = 0.0007). These findings strongly support the incorporation of an IP cisplatin regimen to improve survival in the front-line treatment of stage III, optimally debulked ovarian cancer.